THE USE OF CODE MIXING BY NETIZEN IN THE COMMENTS COLUMN PREWEDDING PHOTO FLARES THAT CAUSED FIRE IN BROMO ON THE “PROBOLINGGOKITA” INSTAGRAM ACCOUNT - Nur Aini, Rofii’atul Fajriyah; Wafa, Hosnol; Tjahyadi, Indra; Andayani, Sri (JURNAL LITERASI, 2024)
This research analyzes the phenomenon of code mixing in digital interaction in Indonesia, focusing on comments on the "probolinggokita" Instagram account. Code mixing is a common occurrence in social media communication, where users combine various languages in a single message. Social media platforms like Instagram facilitate communication with diverse groups of people, where language use can significantly impact social interactions. This research analyzes the code mixing phenomenon by netizen in the comments column prewedding photo flares that caused fire in Bromo "@probolinggokita" on a post about the Bromo Mountain fire incident. The study focuses on identifying types of code-mixing based on Hoffmann's (1991) theory, which includes intra sentential, intra lexical, and involving change of pronunciation code mixing, and combines from each types. This research aims to provide new insights into sociolinguistic phenomena in Instagram comments and understand the factors influencing code mixing usage in social media contexts. This research aims to describe the forms of code mixing that appear in comments on the "probolinggokita" Instagram account. The method used is descriptive-qualitative, with data collection techniques through observation and recording. The data source consists of all comments containing code mixing on the account. Data were analyzed from 64 comments containing code mixing. The analysis results show that there are six significant code mixing patterns: Intra sentential Code Mixing 49 data, Intra lexical Code Mixing 4 data, Involving Change of Pronunciation 5 data, combination of Intra sentential and Intra lexical 2 data, combination of Intra sentential and Involving Change of Pronunciation 2 data, and combination of Intra lexical and Involving Change of Pronunciation 2 data.